2016
DOI: 10.21037/cco.2016.10.01
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder cancer: South American experience

Abstract: Large differences in terms of incidence and mortality due to gallbladder cancer (GBC) have been reported worldwide. Moreover, it seems that GBC has unique characteristics in South America. We surveyed the literature looking for information about the epidemiology, basic and translational research, and clinical trials performed in South America in order to critically analyze the magnitude of this health problem in the region. Compared to other geographic areas, age-standardized mortality rates (ASMR) for GBC in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
8
0
2
Order By: Relevance
“…In Chile and western Argentina, age-standardized mortality rate (ASMR) is high, and in Western countries such as Peru and Ecuador, age-standardized incidence rate (ASIR, equivalent to ASMR) is high. The statistic indicated that people in a range of areas near the Andes are more likely to develop GBC ( 4 ). There are also researches indicated that the Indian Ganges plain in India, the Mapuche Indians in Chile and South America are the most affected areas ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Chile and western Argentina, age-standardized mortality rate (ASMR) is high, and in Western countries such as Peru and Ecuador, age-standardized incidence rate (ASIR, equivalent to ASMR) is high. The statistic indicated that people in a range of areas near the Andes are more likely to develop GBC ( 4 ). There are also researches indicated that the Indian Ganges plain in India, the Mapuche Indians in Chile and South America are the most affected areas ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gallbladder carcinoma is very rare and has a very high mortality rate. Its high prevalence in areas such as South America is attributed especially to the non-modifiable risk factors, in particular, the genetic background [4]. Yet, the most common risk factor worldwide remains chronic cholecystitis due to gallstones.…”
Section: Discussionmentioning
confidence: 99%
“…A family history of gallstone disease accounts for around 25% risk of developing cholelithiasis, a well-established risk factor of GBC, with gallstones found in about 85% of GBC cases [3]. Evidence regarding genetic factors that may also contribute to the development of GBC includes variants of genes related to lipid metabolism such as the rs693 polymorphism of the Apolipoprotein B as well as certain gene variants involved in arsenic metabolism (haplotypes of the Arsenic Methyl Transferase gene AS3MT) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of gallbladder cancer is highest among extrahepatic biliary cancers and is associated with distinct epidemiological features, 1 including high prevalence among women, particularly in countries with a low sociodemographic index 2‐4 ; and high prevalence rates among American Indians and populations in South America, Asia, and the Middle East 2‐3,5‐7 . Genetic factors are thought to contribute to increased risk in some of these populations 8‐10 …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][5][6][7] Genetic factors are thought to contribute to increased risk in some of these populations. [8][9][10] Relying on the presentation and stage of disease, the prognosis of patients with gallbladder cancer varies greatly. Gallbladder cancer is staged using the Tumor, Node, and Metastasis (TNM) system.…”
mentioning
confidence: 99%